Lower Extremity Fractures in Hospitalized Pediatric Patients Following Road Traffic Accidents. Issue 12 (December 2019) - Tenenbaum, Shay; Bariteau, Jason T.; Chechik, Ofir; Givon, Adi; Peleg, Kobi; Thein, Ran
Abstract : Abstract: Lower extremity fractures (LEFs) caused by road traffic accidents (RTAs) can result in significant morbidity and account for a substantial part of nonfatal injuries requiring hospitalization. This study investigated the epidemiology of RTA-associated LEFs in the pediatric population. Based on the National Trauma Registry, data of 28, 924 RTA hospitalized pediatric patients were reviewed. Data were analyzed according to LEF mechanism of injury, age distribution, fracture types, associated injuries, surgical treatment, and their interrelations. A total of 4970 (17.18%) sustained LEFs, with the highest risk for motorcycle-associated RTA, followed by pedestrians. Approximately 1 of 4 patients had multiple fractures. Forty percent (2184 cases) sustained additional injuries, for which car-associated RTAs were at the greatest risk (61%, P < 0.0001), followed by pedestrians and motorcycles (46%–45%, P < 0.0001). Overall, head/neck/face injuries were the most commonly associated injuries. The tibia was the most fractured bone (42%), followed by the femur, fibula, foot, and ankle. This distribution varied according to RTA mechanism. Forty-one percent of cases required fracture treatment in an operating room. As patients were older, the greater the chance they required further treatment in the operating room ( P < 0.0001). This large-scale study on the epidemiology of LEFs in the pediatric population following RTA provides unique information on epidemiological characteristics of LEF, pertinent both to medical care providers and to health policy makers allocating resources and formulating prevention strategies in the attempt to deal with the burden of road traffic accidents. Level of Evidence: Prognostic and epidemiologic study, level II.